2018
DOI: 10.2217/fon-2017-0490
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-20A Upregulates TAK1 and Increases Proliferation in Osteosarcoma Cells

Abstract: Aim:The aim of this study is to explore the function of miR-20a in osteosarcoma. Materials & methods: miR-20a expression was measured by real-time PCR. miR-20a mimics, inhibitor and scramble siRNA were transfected into osteosarcoma cells to observe effects on colony formation and tumor growth. Moreover, relationships of miR-20a with TAK1 were investigated by western blot and luciferase activity. Results: We found that miR-20a was downregulated in osteosarcoma, and overexpression of miR-20a reduced colony forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
(22 reference statements)
1
15
0
1
Order By: Relevance
“…The factors responsible for the development of such premetastatic niches are believed to be directly secreted into the circulation by cells of the primary tumor or to be transported via tumor-shed extracellular vesicles or exosomes and include inflammatory cytokines and chemokines, hormones, proangiogenic factors, extracellular matrix components, metabolites and lipids, as well as genetic material, including DNA, mRNA, and miRNA [19,24]. Among these, miRNAs were shown to alter TAK1 expression levels [25][26][27][28], to regulate b, d, g) from biological sextuplicates (n = 6) (a-d) or from n = 4-6 animals per condition (f, g). *P < 0.05; **P < 0.01; ***P < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…The factors responsible for the development of such premetastatic niches are believed to be directly secreted into the circulation by cells of the primary tumor or to be transported via tumor-shed extracellular vesicles or exosomes and include inflammatory cytokines and chemokines, hormones, proangiogenic factors, extracellular matrix components, metabolites and lipids, as well as genetic material, including DNA, mRNA, and miRNA [19,24]. Among these, miRNAs were shown to alter TAK1 expression levels [25][26][27][28], to regulate b, d, g) from biological sextuplicates (n = 6) (a-d) or from n = 4-6 animals per condition (f, g). *P < 0.05; **P < 0.01; ***P < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GLUT1 is regulated by many factors, such as serine/threonine kinase Akt1 and PI3 signaling, with the most important factor being hypoxia and the transcription factor hypoxia‐inducible factor 1 (HIF‐1) . Studies focused on the function of GLUT1 in tumors showed that GLUT1 promotes proliferation and metastasis and inhibits apoptosis in several cancer types, such as lung cancer and breast cancer . Nevertheless, the expression and function of GLUT1 in PCa cell lines have yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common adult acute leukemia and accounts for ~80% of cases ( 52 ). microRNAs (miRNAs/miRs) are short RNA molecules that negatively regulate gene expression; miRNAs are downregulated in numerous types of solid tumors, such as gastric cancer ( 53 ), lung cancer ( 54 ) and osteosarcoma ( 55 ). Moreover, abnormal expression levels of miRNAs (miR-128a, miR-92a, miR-143 and miR-342) are associated with the development of AML ( 56 , 57 ).…”
Section: Ailanthone (Ail) As An Anti-tumor Drugmentioning
confidence: 99%